Gilteritinib as Bridging and Posttransplant Maintenance for Relapsed Acute Myeloid Leukemia with FLT3-ITD Mutation Accompanied by Extramedullary Disease in Elderly - Saburi, Masuho; Sakata, Masanori; Maruyama, Rika; Kodama, Yosuke; Takata, Hiroyuki; Miyazaki, Yasuhiko; Kawano, Katsuya; Wada, Junpei; Urabe, Shogo; Ohtsuka, Eiichi (Case Reports in Hematology, 2023)
A 69-year-old woman was diagnosed with acute myeloid leukemia (AML) with an FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) mutation. Complete remission (CR) was achieved after induction therapy, but AML resulted in a hematological relapse two months after the consolidation chemotherapy. Relapse was accompanied by multiple skin lesions that demonstrated leukemic cell infiltration as well as a drooping right eyelid with extroversion of the eye due to right oculomotor palsy. Gilteritinib was started as salvage therapy, and bone marrow blasts decreased to 0.8% after one month. Two months later, the eye symptoms improved, and the patient underwent cord blood transplantation (CBT). The skin lesions disappeared after the conditioning regimen, and the patient achieved CR status with complete donor chimerism at day 28. Gilteritinib was restarted as posttransplant maintenance therapy on day 53 of CBT. No adverse events other than mild hepatotoxicity were observed, and the patient was alive and in CR status, while continuing gilteritinib at one year and seven months after CBT. Bridging and posttransplant maintenance therapy with gilteritinib may be a promising therapeutic option for relapsed AML with the FLT3-ITD mutation in elderly patients.